PREVALENCE OF COCCIDIA IN RABBIT IN MIDDLE GUJARAT - Hirani , N D; Solanki , J B (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A detailed study on the prevalence of coccidial infection in domestic rabbits belonging to various age groups, sex and season was undertaken at Vadodara and Surat district over a period of one year. The prevalence of coccidial infection in rabbits, based on 431 faecal samples examined, was found to be 29.00 per cent, predominantly in young stock below three months of age. Females harboured more infection than the males. Prevalence was seen more in monsoon followed by winter and summer season. Five species of coccidia identified were Eimeria magna, E. media, E. intestinalis, E. coecicola, and E. piriformis.